Prevalence, contributing factors and consequences of unethical practices among university students in Edo State, Nigeria: Prevalence, contributing factors and consequences of unethical practices among university students in Edo State, Nigeria (Journal of Educational Management, 2021)
This study investigated the prevalence, contributing factors and consequences of unethical practices among university students in Edo State, Nigeria. Three research questions guided the study. The descriptive survey design was adopted for this study. The population of the study comprised all full-time undergraduates and lecturers in public and privately-owned universities in Edo State. Using a multistage sampling procedure, a sample of 720 students and 200 lecturers was drawn for the study. Data were collected through two questionnaires entitled "Unethical Practices among University Students Questionnaire: (UPUSQ) and "Unethical Practices and University Education Questionnaire" (UPUEQ). The instruments were face-validated by two other experts in Measurement and Evaluation in the Faculty of Education, University of Benin. A reliability testing of the instruments was done using Cronbach’s Alpha. The results of the study revealed, among others, that all the identified unethical practices except vandalism and thethreat and actual kidnapping of lecturers by students were moderately prevalent among university students in Edo State. Findings further revealed that students’desperation to pass examinations at all cost, excess workload on students, poor policy implementation and negative peer influence were the main contributing factors to university students’involvement in unethical practices in Edo State. Based on the findings of this study, the authors recommended, inter alia, that reported cases of unethical practices should be promptly addressed and thoroughly investigated, and that defaulters should be sanctioned or punished by each university’s rules and regulations for such offences or by-laws stipulated for such offences
Keywords: unethical practices; prevalence; contributing factors